Characterization of the deformation state of magnesium by electrical resistance. (1st July 2022) - Meyer, Sebastian; Wiese, Björn; Hort, Norbert; Willumeit-Römer, Regine
Graphical abstract: Abstract: Electrical resistance testing offers a fast and non-destructive method, which is very sensitive to microstructural features and crystal defects. The influence of the mechanically introduced strain, the alloy concentration and solution state as well as the grain size is shown and discussed based on cold-drawn magnesium wires containing 0.45, 0.91 and 1.42 at. % silver. The condition of the material can be quantified by linear increase of 8.96  ±  0.17 n Ω m per unit strain and 6.58  ± 0.06 n Ω m/at. % with silver content. This enables the classification of the deformation state and work hardening to push the process limits and allow adjusting the mechanical properties for their application.